Development of a Simplified Dynamic Testing Device for Turfed Sports Surfaces - Caple, Matt C. J.; James, Iain T.; Bartlett, Mark D.; Bartlett, David I. (Professional Engineering Publishing, 2011)
The response of natural turf surfaces to loading changes with the force and loading rate applied. Quantification of surface behaviour to athlete loading is complicated by the lack of devices that replicate forces, stresses and loading rates of athletes that can be specifically used on natural turf. To address this issue, a vertical dynamic impact testing device, the DST, was developed. The DST consists of a compressed air driven ram which vertically impacts a studded test foot onto the surface using data from biomechanical studies. The vertical dynamic stress of athlete foot strike during running is replicated, using peak force and mean boot contact area data. The ram pressure is adjustable to allow variation of the stress applied upon impact, potentially replicating a range of athlete-surface interactions. Initial laboratory testing indicated that the device was sensitive to changes in soil condition due to variations in impact data. Total penetration time and distance, and surface energy absorption were all significantly greater in prepared ‘soft' soil treatments (p<0.05). Loading rate in the first 50 ms after impact was significantly greater in the ‘hardest' soil treatment (p<0.05). Future research work will determine in-situ behaviour of actual playing surfaces, compare device loading rates to those of athletes, and assess surfaces to a range of stres
Keywords: Natural turf, dynamic soil strength, test device, athlete-surface interaction